ANALISIS PERGESERAN NILAI BUDAYA SENI JONGGAN PADA MASYARAKAT DAYAK KANAYATN (MORO BETUNG KABUPATEN LANDAK) - Teo Romondo Paskalis; Agus Sastrawan Noor; Rustiyarso Rustiyarso (Universitas Tanjungpura, 2019)
AbstractThis research aimed to describe the transition of cultural value of Jonggan arts on Dayak Kanayatn’s community (A study at Dusun Moro Betung, Kabupaten Landak). This research was descriptive with ethnography-qualitative. Techniques of data collection were observation, interview, and documentation. Instruments of data collection were in forms of guided observation, guided interview, and documents. Supplementary intruments were in the forms of two smartphones which functioned as voice recorder and audio-visual recorder. Testing data validity was conducted by applying triangulation technique. The results showed that the transition of Jonggan arts cultural value was caused by internal and external factors. Internal factor was affected by the role of studio leader, Jonggan member, the community, and local government. The transitions of cultural value happening comprised; (1) free dance, (2) duration of Jonggan Arts performance, (3) dancer’s costume, (4) dancer’s cosmetics, (5) dancer’s property, and (6) ticket existence. External factors were affected by; (1) the incoming culture of gambling, (2) music player, (3) trending musics, and (4) soundsystem. Keywords: Transition of Cultural Value, Jonggan Arts, Dayak Kanayatn